PERAN DINAS SOSIAL DALAM MENANGGULANGI PENGEMIS DI KOTA BANDA ACEH - Zamharira, Cut; Arantika, Desi Puspita (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
This study aims to determine the efforts made by the social service in overcoming the growing number of beggars in Banda Aceh and the obstacles faced in the process of overcoming them. The research method used in this study is descriptive qualitative. Where researchers seek deeper information related to the steps, obstacles and support faced by the social service in an effort to bring order to beggars in Banda Aceh City. While the technique of data collection is done through participant observation, interviews and documentation. The data analysis stage begins with reducing data, presenting and concluding it. The results showed that the city of Banda Aceh's social services had carried out their roles in the form of data collection, supervision and guidance for beggars. But in its implementation there are still some obstacles, among others, lack of coordination and laws governing the prohibition of begging.